Creation Ex Nihilo as Mixed Metaphor. (25th March 2013) - Tanner, Kathryn
Abstract This article makes the following three programmatic points. First, an understanding of divine transcendence, prominent in Christian theology's apophatic strain, developed in tandem, both historically and logically, with ideas about creation that eventuated in a creation ex nihilo viewpoint. Such an account of divine transcendence, second, fosters an account of creation (and a general understanding of the God/world relationship) that typically mixes both natural and personalistic images and categories. The loss of such an account of transcendence since the early modern period, I suggest thirdly and in conclusion, is therefore responsible in great part for the dualistic, mutually exclusive alternation between a deistic, interventionist God and pan(en)theism so common in modern Christian thought.